USE OF 'LIME' ORANGE AND THEIR WASTES IN THE DEVELOPMENT OF NEW PRODUCTS - de Farias Silva, C. E.; da Gama, B. M. V.; Oliveira, L. M. T. de M.; de Araujo, L. T.; de Araujo, M. L.; de Oliveira Junior, A. M.; Abud, A. K. de S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
One of the great humanity challenges is to balance production of goods and services, economic growth, social equity and environmental sustainability. Alternatively, the industrialization of food can contribute markedly to the encouragement and stabilizing agricultural production, allowing better use of surplus and promoting their use throughout the year and not just in times of harvest. Allied to this, biotechnological processes enable not only the utilization of the feedstock but also its residues in the development of new products. The culture of orange Lima has the municipality of Santana do Mundaú, in Alagoas, the main reference and Brazilian production center. The excellent environmental conditions in the region allow the development of excellent fruit quality and ample opportunities to compete with those produced in other regions. However, even though it presents advantages and facilities, investments in the citrus industry are limited, resulting in low levels of productivity and discard of the surplus product of the region. This work aimed the use of biotechnological technologies to propose orange Lima utilization in a point of industrial view, assessing the commercial viability and acceptance of the Lima orange wine and vinegar, obtained from the juice, essential oil extraction from the bark and the use of albedo, coming from the extraction process, for the production of pectin, incorporation into food, adsorption, enzyme production and 2G ethanol. Products of economic value were generated, adding value to a waste material and providing an alternative income source, thereby fulfilling an environmental and social function.